The mental health of fire-fighters: An examination of the impact of repeated trauma exposure. (July 2016) - Harvey, Samuel B; Milligan-Saville, Josie S; Paterson, Helen M; Harkness, Emily L; Marsh, Annabel M; Dobson, Mark; Kemp, Richard; Bryant, Richard A
Objective: Emergency workers, such as fire-fighters, are routinely exposed to potentially traumatic events. While a number of studies have examined the occurrence of post-traumatic stress disorder, the role of multiple traumas on other mental health sequelae, such as depression and alcohol misuse, among emergency workers remains unclear. This study aimed to assess the prevalence of post-traumatic stress disorder, depression and alcohol misuse in a sample of current and retired fire-fighters and examine their relationship with cumulative trauma exposure. Method: A cross-sectional survey was completed by current ( n = 488) and retired ( n = 265) fire-fighters from Fire and Rescue New South Wales, Australia. Demographic and occupational information was collected, including the number of fatal incidents fire-fighters reported attending across years of service. Validated, self-report measures were used to determine probable caseness for post-traumatic stress disorder, depression and heavy drinking. Results: Among current fire-fighters, rates of post-traumatic stress disorder and depression were 8% and 5%, respectively, while 4% reported consumption of more than 42 alcoholic drinks per week. Retired fire-fighters reported significantly greater levels of symptomatology, with the prevalence estimates of post-traumatic stress disorder at 18% ( p = 0.001), depression at 18% ( p < 0.001) and heavy drinking at 7%. There was a significant positive linear relationship between the number of fatal incidents attended and rates of post-traumatic stress disorder, depression and heavy drinking. Conclusion: Fire-fighters suffer from high rates of mental disorders, with rates of post-traumatic stress disorder, depression and heavy drinking continuing to rise in a linear manner with each additional trauma exposure. The level of psychiatric morbidity among retired fire-fighters appears to be particularly high. Our findings have important implications for the ongoing debates surrounding the detection of mental disorders in high-risk occupations and for policy considerations around the welfare of current and retired emergency workers.